Characterization and Classification of Sugarcane Growing Soils of North Coastal Districts of Andhra Pradesh - A. Sireesha; M. Bharatha Lakshmi, Ch. S. Rama Lakshmi*, T. Sreelatha (Journal of the Indian Society of Soil Science, 2021)
Twelve Typical pedons from sugarcane growing soils of Visakhapatnam, Vizianagaram and Srikakulam district were studied for their morphological characteristics, physical, physicochemical and chemical properties and classified as per USDA soil taxonomy. All the pedons were confined to semi-arid mansoonic climate and occur on low lying to plain lands. The soils were deep with coarse texture in sandy soils and clay loam texture in black soils. Single grain to sub-angular blocky structure, wet consistence of nonsticky, non plastic to plastic, sticky were the other features recognized. The results of physicochemical properties revealed that all the soils were neutral to moderately alkaline in soil reaction with non-saline conductivity. Among all the exchangeable bases calcium was the dominant cation followed by magnesium, potassium and sodium. All the surface layers exhibited low to medium in available nitrogen status and medium to high in available phosphorus and potassium status. Available copper and manganese in all pedons were above critical limits. Sufficiency in available zinc and iron status (except pedon 8-12) was observed in all the surface layers. The study area falls under ustic moisture and isohyperthermic temperature regimes. The mineralogy is mixed type. The pedons of Visakhapatnam district are classified as fine loamy, mixed, isohyperthermic, Typic Haplustepts and coarse loamy, mixed isohyperthermic, Typic Haplustepts.